2019
DOI: 10.12688/wellcomeopenres.15599.1
|View full text |Cite
|
Sign up to set email alerts
|

Consensus-based statements for the management of mitochondrial stroke-like episodes

Abstract: Focal-onset seizures and encephalopathy are prominent Background: features of a stroke-like episode, which is a severe neurological manifestation associated with subtypes of mitochondrial disease. Despite more than 30 years of research, the acute treatment of stroke-like episodes remains controversial.We used the modified Delphi process to harness the clinical Methods: expertise of a group of mitochondrial disease specialists from five European countries to produce consensus guidance for the acute management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 39 publications
1
78
0
3
Order By: Relevance
“…However, mitochondrial dysfunction attenuates platelet survival and increases the risk for thrombovascular events (Kunz et al, 2017;Melchinger et al, 2019), increasing stroke risk (Behrouzi and Punter, 2018). Mitochondrial dysfunction may cause stroke-like episodes independent of hypoxia (Ng et al, 2019). Therefore, spaceflight-induced mitochondrial dysfunction could increase cardiovascular disease risk in longterm missions caused by microgravity cardiovascular deconditioning and space radiation (Hughson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, mitochondrial dysfunction attenuates platelet survival and increases the risk for thrombovascular events (Kunz et al, 2017;Melchinger et al, 2019), increasing stroke risk (Behrouzi and Punter, 2018). Mitochondrial dysfunction may cause stroke-like episodes independent of hypoxia (Ng et al, 2019). Therefore, spaceflight-induced mitochondrial dysfunction could increase cardiovascular disease risk in longterm missions caused by microgravity cardiovascular deconditioning and space radiation (Hughson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…First, not all patients with a mitochondrial disorder (MID) who ever experienced a SLL also have an individual history positive for epilepsy 2 . Thus, we disagree with the statement that "seizures are commonly present at the outset of strokelike episodes (SLEs)" 1 . Second, the electroencephalography during a SLL does not reveal epileptogenic activity in most cases 3 .…”
Section: Correspondencementioning
confidence: 58%
“…We read with interest the consensus statement by Ng et al about the pathogenesis and treatment of stroke-like lesions (SLLs) 1 . We largely disagree with the consensus paper as it does not consider arguments for alternative pathomechanisms explaining the development of a SLL.…”
Section: Correspondencementioning
confidence: 99%
“…Most adult patients present to general neurology clinics with slowly progressive neurological symptoms, such as chronic progressive external ophthalmoplegia, myopathy, neuropathy and ataxia. However, neurologists need to be aware that the acute presentations of mitochondrial disease, such as stroke-like episodes and refractory focal-onset seizures, 3 can mimic other commoner neurological disorders, such as ischaemic stroke, infective/immune-mediated encephalitis and CNS demyelinating/inflammatory diseases. The initial description of MELAS syndrome suggested that the stroke-like episodes predominantly affect people aged less than 40 years.…”
mentioning
confidence: 99%
“…7 Currently, there is no proven effective disease-modifying therapy for the stroke-like episodes; aggressive seizure management remains the most crucial step to protect patients’ cerebral function. 3…”
mentioning
confidence: 99%